Efficacy and safety of long-term continuous nirogacestat treatment in adults with desmoid tumors: results from the DeFi trial : clinical trial updates - Ratan, Ravin; Kasper, Bernd; Alcindor, Thierry; Schöffski, Patrick; van der Graaf, Winette T.A.; Federman, Noah; Bui, Nam Q.; D'Amato, Gina; Riedel, Richard F.; Attia, Steven; Chawla, Sant; Lim, Allison; et al. (Journal of clinical oncology, 2025)
In the phase III placebo-controlled DeFi trial (ClinicalTrials.gov identifier: NCT03785964) primary analysis, nirogacestat showed significant improvement versus placebo in progression-free survival (PFS), objective response rate (ORR), and patient-reported outcomes (PRO) in adult patients with progressing desmoid tumors (DT; median [range] exposure: 20.6 [0.3-33.6] months). Here, long-term nirogacestat efficacy and safety were evaluated in patients randomly assigned to nirogacestat and followed through the final data cutoff date of December 19, 2024. End points included PFS and ORR per RECIST v1.1, PRO, and safety. The median (range) duration of exposure was 33.6 (0.3-61.8) months. Median PFS was not reached. The ORR with up to 4 years of nirogacestat treatment was 45.7% (32 of 70), with three additional partial and three additional complete responses since the primary analysis. Further target tumor size reduction occurred in most patients. Benefits in PROs were sustained while on treatment. Frequently reported treatment-emergent adverse events (TEAEs) decreased in incidence and severity over time. Since the primary analysis, four patients discontinued nirogacestat because of TEAEs between years 2 and 4. In conclusion, long-term continuous nirogacestat treatment was associated with further tumor size reductions, durable objective responses, sustained PRO benefits, and a manageable safety profile consistent with the primary analysis.